2018
DOI: 10.1242/jeb.176644
|View full text |Cite
|
Sign up to set email alerts
|

Impaired associative learning after chronic exposure to pesticides in young adult honey bees

Abstract: Neonicotinoids are the most widespread insecticides in agriculture, preferred for their low toxicity to mammals and their systemic nature. Nevertheless, there have been increasing concerns regarding their impact on non-target organisms. Glyphosate is also widely used in crops and, therefore, traces of this pesticide are likely to be found together with neonicotinoids. Although glyphosate is considered a herbicide, adverse effects have been found on animal species, including honey bees. is one of the most impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 52 publications
3
26
0
1
Order By: Relevance
“…3% w/v) but not with high concentrations (e.g. 30% w/v; Aliouane et al, 2009 ; Demares et al, 2018 ; Eiri and Nieh, 2016 ; Mengoni Goñalons and Farina, 2015 , 2018 ). Based on these published studies, we expected that perception of the unconditioned stimuli in our experiments would not be affected by neonicotinoid exposure, as we used very concentrated sucrose as one of our unconditioned stimuli (34% w/v sucrose).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…3% w/v) but not with high concentrations (e.g. 30% w/v; Aliouane et al, 2009 ; Demares et al, 2018 ; Eiri and Nieh, 2016 ; Mengoni Goñalons and Farina, 2015 , 2018 ). Based on these published studies, we expected that perception of the unconditioned stimuli in our experiments would not be affected by neonicotinoid exposure, as we used very concentrated sucrose as one of our unconditioned stimuli (34% w/v sucrose).…”
Section: Discussionmentioning
confidence: 88%
“…Bumblebees fed an acute dose of IMD prior to a task had difficulty learning to distinguish artificial flowers with different scents ( Muth and Leonard, 2019 ). Young worker honeybees between 5 and 14 days old exposed to IMD over longer periods (5–14 days) had slower rates of learning in both simple and differential learning tasks ( Mengoni Goñalons and Farina, 2018 ). Others have found that IMD at a similar dose reduces the rate of acquisition during aversive learning using cues mimicking a predatory attack ( Tan et al, 2014 ; Zhang and Nieh, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that, under laboratory conditions and without pathogen challenge, only the higher doses of glyphosate (0.1 mM and 1.0 mM) reduced the life span of young worker bees. In studies that did not examine the role of gut microbiota, glyphosate was shown to directly compromise larval development and adult behavior (12,(42)(43)(44)(45), although some other studies failed to detect effects on survivorship (20,46,47). Tylosin, which had large effects on the gut microbiota, increased mortality in only one of the four trials with caged laboratory bees (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the honeybee, glyphosate or Roundup formulation can induce an increase in lipid peroxidation, a decrease in β-carotene and derived antioxidants, and a reduction in acetylcholine esterase activity [13,1921]. A chronic exposure to the herbicide can reduce the honeybee learning performance while acute exposure was shown to reduce its short-term memory [22,23]. Glyphosate can also affect the honeybee navigation by increasing the time and path of homeward flight [24].…”
Section: Introductionmentioning
confidence: 99%